MOISTURE CONTENT MEASUREMENT IN GELATIN: A COMPARISON OF GRAVIMETRIC METHODS USING MOISTURE ANALYZER AND OVEN - Warmiati; Dewi Nurhidayati (Politek ATK Yogyakarta Press, 2024)
The measurement of water content in gelatin samples in the practical activities in the Instrumentation and Polymer Engineering Laboratory is conducted using the gravimetric method with the Moisture Analyzer Sartorius Type MA 45. Meanwhile, the method acknowledged and approved by AOAC International is the Oven method. This research aims to compare the measurement results of the Moisture Analyzer with the reference method, namely the Oven method referring to AOAC, to determine if there is a statistically significant difference in the results. The results of both methods are compared using a paired T-test, yielding a calculated T-value (Tstat) of 0.7519 and a tabulated T-value of 2.2622. These results indicate that Tstat ≤ the tabulated T-value at a 95% confidence level, thus accepting the null hypothesis (H0). This suggests that μa=μb, meaning that there is no significant difference between the two methods. The precision test results for both methods also meet the criteria, with %RSD ≤ 2% and %RSD ≤ 2/3 CV Horwitz.